Flexibility in Spanish elite inline hockey players: Profile, sex, tightness and asymmetry - Cejudo, A.; Moreno-Alcaraz, V. J.; Izzo, R.; Robles-Palazón, F. J.; Sainz de Baranda, P.; Santonja-Medina, F. (International Journal of Environmental Research and Public Health, 2020)
Limited ranges of motion (ROM) have been considered as a relevant risk factor for team sports injuries. The main purposes of the current study were to describe the lower extremity ROM profile, muscular tightness and asymmetries in elite inline hockey players and to examine sex-related differences. Twenty professional inline hockey players from 2 Spanish National Teams (male and female) were measured of passive hip extension [HE], hip adduction with hip flexed 90° [HAD-HF], hip flexion with the knee flexed [HF-KF] and extended [HF-KE], hip abduction with the hip neutral [HAB] and hip flexed 90° [HAB-HF], hip external [HER] and internal [HIR] rotation, knee flexion [KF], ankle dorsiflexion with the knee flexed [ADF-KF] and extended [ADF-KE] ROMs of the dominant and non-dominant leg ROMs were taken. A paired t-test was carried out to assess asymmetries. ROM values were classified as "normal versus tightness", and "normal versus asymmetry" according to the proposed reference values. The effect size for each variable was analyzed. Male team exhibited asymmetry in HF-KF (133.2° dominant vs. 129.8° non-dominant; p = 0.042; d = 0.7243 [moderate effect sizes]) and female team in ADF-KF (38.8° dominant vs. 41.0 non-dominant; p = 0.001; d = 0.6 [moderate effect sizes]) and HAB ROM (41.2° dominant vs. 38.8 non-dominant; p = 0.005; d = 1.1767 [moderate effect sizes]). Male players reported asymmetry in HAD-HF (n = 5), HER (n = 4) and HE (n = 3), whereas female players presented asymmetries in HER (n = 4), HE (n = 3) and KF (n = 2). Overall, 20-100% of all participants showed limited KF, HF_KE, HIR, HE, ADF_KF, HAD-HF, HF-KF, ADF_KE, HTR and HER ROM. The results of this study reinforce the requirement of prescribing exercises aimed at improving hip, knee and ankle ROM within everyday inline hockey practices. In addition, as some asymmetries were found, unilateral flexibility training should be considered where appropriate.